PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAAN DI PT. BALI COSME INDO PERKASA - Putri Dayu Rara (STIE BIITM, 2019)
The Title Research is The Influence of Leadership and Work Motivation On Employee Performance at PT. Bali Cosme Indo Perkasa. Employee performance is the most important thing to be considered by the company, because it can affect the achievement of company goals and progress to survive in a global competition that often changes or is unstable. The things that can affect employee performance are leadership and work motivation of employees. This research aimed to analyze the influence of Leadership and Work Motivation On Employee Performance at PT. Bali Cosme Indo Perkasa. The sample of this research is 35 respondents of employees at PT. Bali Cosme Indo Perkasa. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the leadership and work motivation influenced on employee performance based on hypothesis testing with the F and t test results, it can be concluded that the leadership variable (X1) and work motivation (X2) simultaneously (together and significantly influence on employee performance variable (Y) with value of F-test is 47,604 and sig 0,000. The leadership variable (X1) partially and significantly positive influenced on employee performance (Y) with value of t-test is 5,218 and sig. 0,000 and work motivation variable (X2) significantly positive influenced on employee performance variable (Y) with value of t-test is 5,084 and sig. 0,000 at PT. Bali Cosme Indo Perkasa.